Anti‐VEGF antibody delivered locally reduces bony bar formation following physeal injury in rats. Issue 8 (24th November 2020) - Erickson, Christopher B.; Newsom, Jake P.; Fletcher, Nathan A.; Yu, Yangyi; Rodriguez‐Fontan, Francisco; Weatherford, Shane A.; Hadley‐Miller, Nancy; Krebs, Melissa D.; Payne, Karin A.
Abstract: Physeal injuries can result in the formation of a "bony bar" which can lead to bone growth arrest and deformities in children. Vascular endothelial growth factor (VEGF) has been shown to play a role in bony bar formation, making it a potential target to inhibit bony repair tissue after physeal injury. The goal of this study was to investigate whether the local delivery of anti‐VEGF antibody (α‐VEGF; 7.5 μg) from alginate:chitosan hydrogels to the tibial physeal injury site in rats prevents bony bar formation. We tested the effects of quick or delayed delivery of α‐VEGF using both 90:10 and 50:50 ratio alginate:chitosan hydrogels, respectively. Male and female 6‐week‐old Sprague‐Dawley rats received a tibial physeal injury and the injured site injected with alginate‐chitosan hydrogels: (1) 90:10 (Quick Release); (2) 90:10 + α‐VEGF (Quick Release + α‐VEGF); (3) 50:50 (Slow Release); (4) 50:50 +  α‐VEGF (Slow Release +  α‐VEGF); or (5) Untreated. At 2, 4, and 24 weeks postinjury, animals were euthanized and tibiae assessed for bony bar and vessel formation, repair tissue type, and limb lengthening. Our results indicate that Quick Release + α‐VEGF reduced bony bar and vessel formation, while also increasing cartilage repair tissue. Further, the quick release of α‐VEGF neither affected limb lengthening nor caused deleterious side‐effects in the adjacent, uninjured physis. This α‐VEGF treatment, which inhibits bony bar formation without interfering with normal bone elongation, could have positive implications for children suffering from physeal injuries.